Platelet Microparticles Enriched in miR-223 Reduce ICAM-1-Dependent Vascular Inflammation in Septic Conditions - Szilágyi, Bernadett; Fejes, Zsolt; Rusznyák, Ágnes; Fenyvesi, Ferenc; Pócsi, Marianna; Halmi, Sándor; Griger, Zoltán; Kunapuli, Satya P.; Kappelmayer, János; Nagy, Béla (Frontiers in Physiology, 2021)
In the process of sepsis, activated platelets shed microvesicles containing microRNAs (miRNAs), which can be internalized by distinct recipient cells in circulation, consequently eliciting a potent capability to regulate their cellular functions in different diseases. In the present study, activated human platelets transferring miR-223 into endothelial cells via platelet-derived microparticles (PMPs) was investigated in vitro during septic conditions with a proposed mechanism involving in downregulation of the enhanced expression of intercellular adhesion molecule-1 (ICAM-1). The uptake of PMPs encasing miR-223 and the adhesion of peripheral blood mononuclear cells (PBMCs) on human coronary artery endothelial cells (HCAECs) were observed by immunofluorescence microscopy upon co-culture with PMPs isolated from sepsis or control plasma. The expression of miR-223-3p and its gene target ICAM1 in HCAECs were quantified by RT-qPCR and ELISA after the cells were incubated with septic or control PMPs, whose levels were induced with thrombin-receptor activating peptide (TRAP). Leukocyte-depleted platelets (LDPs) from septic patients showed a decreased miR-223 level, while septic plasma and PMPs revealed an elevated miRNA level compared to control samples. Similarly, TRAP-activated LDPs demonstrated a reduced intracellular miR-223 expression, while increased levels in the supernatant and PMP isolates were observed vs. untreated samples. Furthermore, TNF-a alone resulted in decreased miR-223 and elevated ICAM1 levels in HCAECs, while PMPs raised the miRNA level that was associated with downregulated ICAM1 expression at both mRNA and protein levels under TNF-a treatment. Importantly, miR-223 was turned out not to be newly synthesized as shown in unchanged pre-miR-223 level, and mature miR-223 expression was also elevated in the presence of PMPs in HCAECs after transfection with Dicer1 siRNA. In addition, septic PMPs containing miR-223 decreased ICAM1 with a reduction of PBMC binding to HCAECs. In conclusion, septic platelets released PMPs carrying functional miR-223 lower ICAM1 expression in endothelial cells, which may be a protective role against excessive sepsis-induced vascular inflammation.